2015
DOI: 10.1111/nph.13239
|View full text |Cite
|
Sign up to set email alerts
|

Preferential allocation, physio‐evolutionary feedbacks, and the stability and environmental patterns of mutualism between plants and their root symbionts

Abstract: SummaryThe common occurrence of mutualistic interactions between plants and root symbionts is problematic. As the delivery of benefit to hosts involves costs to symbionts, symbionts that provide reduced benefit to their host are expected to increase in frequency. Plants have been shown to allocate preferentially to the most efficient symbiont and this preferential allocation may stabilize the mutualism.I construct a general model of the interactive feedbacks of host preferential allocation and the dynamics of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
162
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(174 citation statements)
references
References 96 publications
10
162
2
Order By: Relevance
“…Under high P availability or low light conditions, the coexistence of two root symbionts becomes a burden for the plant host (Ballhorn et al, 2016). Indirect support for this theory can be observed in the suppression of root colonization by AM fungus in most of the plant–substrate treatments with increasing P-fertilization ( Figure 2 ), which is consistent with the preferential allocation hypothesis (Bever, 2015). …”
Section: Discussionsupporting
confidence: 82%
“…Under high P availability or low light conditions, the coexistence of two root symbionts becomes a burden for the plant host (Ballhorn et al, 2016). Indirect support for this theory can be observed in the suppression of root colonization by AM fungus in most of the plant–substrate treatments with increasing P-fertilization ( Figure 2 ), which is consistent with the preferential allocation hypothesis (Bever, 2015). …”
Section: Discussionsupporting
confidence: 82%
“…However, whether Glomus species in our study site are weak competitors for carbohydrates or whether they just have very strong host specificity remain to be determined through further investigation. Although competition can sometimes produce a phylogenetically clustered pattern even when functional traits are phylogenetically conserved (Mayfield and Levine, 2010), in our case, a clustered pattern in unfertilized soil can be largely attributed to environmental filtering, because plants under extremely low P availability (<3 mg kg À1 soil in our study site) can be expected to actively select AM fungi with high P-uptake ability (Kiers et al, 2011;Bever, 2015), which has been shown to be phylogenetically conserved (Powell et al, 2009). , the significant differences between columns are indicated with dissimilar letters using Tukey's HSD test (P 0.05) after fitting linear mixed effects models.…”
Section: Fertilization Effects On Phylogenetic Structure Of Am Fungi mentioning
confidence: 67%
“…Second, because species of AM fungi have different niches and are known to prefer to inhabit different soil conditions (Schechter and Bruns, 2008;Alguacil et al, 2010;Dumbrell et al, 2010), fertilization may directly select taxa that grow best in the enriched conditions. Third, there is good evidence that plants actively select AM fungal taxa that best provision nutrients (Parniske, 2008;Kiers et al, 2011;Bever, 2015) and many field studies have shown that certain plants select particular AM fungi (e.g. Vandenkoornhuyse et al, 2003;Veresoglou and Rillig, 2014); thus, the loss of plant species caused by fertilization can lead to significant changes in the AM fungal community (Liu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…[31,37]). Our model also does not consider the impact of imperfect mixing in the partner community-a process that could lead to positive associations and repeat encounters among the offspring of individual modules.…”
Section: Discussionmentioning
confidence: 99%